Inculcating secure coding for beginners - A. Aziz, Normaziah; Hassan, Nur Asnida; Shamsuddin, Siti Nurul Zulaikha (IEEE, 2017)
This paper describes an implementation of a Secure Coding learning package for Undergraduate students in the Kulliyyah of Information and Communication Technology (KICT) at the International Islamic University Malaysia. The learning package consists of three components which are SCALT, WebGoat and notes on several vulnerabilities in programming languages. This work aims to create awareness among the KICT community on the importance of secure coding in any application development. This package teaches individuals on how hackers take advantage on vulnerabilities that exist on web applications and allows students to experience within the WebGoat environment. Tips on handling vulnerabilities when coding in C, C++ and Java are also provided for students’ reference. This learning package is an effort to inculcate students at an early age of software developers, to produce secure applications.